Fabrication and characterization of poly(ε-caprolactone)/gelatin nanofibrous scaffolds for retinal tissue engineering. Issue 1 (2nd January 2018) - Rahmani, Shiva; Tabandeh, Fatemeh; Faghihi, Shahab; Amoabediny, Ghassem; Shakibaie, Mehdi; Noorani, Behnam; Yazdian, Fatemeh
ABSTRACT: Different ratios of poly(ε-caprolactone) (PCL) and gelatinwere used to fabricate scaffolds for regeneration of retinal pigment epithelium (RPE) layer. Physical and chemical characterizations were performed and the behavior of human RPE cells on the scaffolds was evaluated subsequently. An increase in gelatin content in the scaffold enhanced hydrophilicity, RPE cell attachment, proliferation, and spreading over PCL scaffolds. Granular and cytoplasmic expressions of RPE65 and Cytokeratin 8/18 markers confirmed the presence of RPE cells. It was believed that PCL/gelatin scaffolds could be used as substrates to replace RPE extracellular matrix to facilitate regeneration of RPE layer in retinal diseases. GRAPHICAL ABSTRACT: